Providing the bivariate anomaly map of Cu–Mo and Pb–Zn using combination of statistic methods in Parkam district, Iran - Ghannadpour, Seyed Saeed; Hezarkhani, A. (Springer, 2017)
U-statistic method is one of the most important univariate structural methods which considers spatial situation of samples. The U-statistic method could be combined with other methods because it devotes a new value to each sample. However, this method separates anomaly based on one variable. The goal in present study is to use and extend this method in multivariate mode. For this purpose, the U-statistic method should be combined with a multivariate method which devotes a new value to each sample based on several variables. Therefore, the U-statistic was applied on Mahalanobis distance values of samples because Mahalanobis distance is calculated based on several variables. This method is a combination of efficient U-statistic and Mahalanobis distance and is used for the first time. Combination results for Cu, Mo, Pb and Zn elements in Parkam district, Kerman, Iran, led to better performance of these two methods. Results show that samples indicated by the combination of these methods as anomalous are more regular; less dispersed and are more accurate than using just one of them. Also it was observed that combination results (especially for Cu and Mo) are closely associated with the defined zone of potassic alteration in the study area. Finally, bivariate lithogeochemical maps of the study area are provided for Cu–Mo and Pb–Zn which have been prepared using combination of the U-statistic and the Mahalanobis distance methods.